Message - El-Zahaby, Dr. Sally A. (Universal Journal of Pharmaceutical Research, 2019)
It would like to thank as well the editor-in-chief for the invitation and the opportunity given to me to write this letter. UJPR is growing every year with lots of published researches covering many scientific disciplines. One of the outstanding key for this success is the healthy team work environment within the board. Every member is doing his role perfectly and on time. The UJPR managing team, is very helpful, responding promptly to us, and always sharing with the board every detail. UJPR is an international journal that gathers editors and researchers from all over the world. Editorial Board members originates from different countries like; India, China, Egypt, Nigeria, Malaysia, Ireland, Indonesia, Hungary, United States, Switzerland, Italy, Spain, Saudi Arabia, Syria, United Kingdom, South Africa, Iraq, and Brazil. Authors originated from Nigeria, Egypt, India, China, and many others. Universal Journal of Pharmaceutical Research publish research articles of diverse scientific interests; Pharmacy and pharmaceutical sciences, Pharmacology, infectious diseases, molecular cardiology, immunopharmacology, inflammation, gastrointestinal and urogenital diseases, molecular mechanisms of action of various synthetic and natural occurring drugs., apoptotic inducers from plants, microbes and marine organisms, design and development of drugs, bioactivity of plant extracts, microbial extracts, their chemical standardization using different analytical techniques, medicinal plants growing in Asia-Pacific region, their chemical standardization, isolation of medicinal agents from these plants and their role with regard to global health issues, safety valuation, pre-clinical toxicology, interaction with drugs and harmful events of herbal preparations and Pharmacokinetics and pharmacodynamics of natural compounds. UJPR is also indexed and abstracted in more than 40 well known indexing services including Google Scholar, CAS, CASSI (American Chemical Society), BASE, Directory of Science, ROAD, ICV and many more. The journal had 158 citations until November 2019. UJPR’s website is very well organized and informative. It is easy to use and number of visitors are increasing daily. I can expect that Universal Journal of Pharmaceutical Research will have soon a good impact factor because of the dedicated editors and reviewers and the author’s contributions.